The Interpretation of Legal Principles by the Government in the Special Autonomous Region of Aceh - Muhammad Reza Maulana; Zainal Abidin; Mazwar Mazwar (International Journal of Law and Society, 2026)
Law Number 11 of 2006 on the Governance of Aceh embodies the principle of lex specialis due to its territorial scope, while Law Number 4 of 2009 on Mineral and Coal Mining also contains a lex specialis character as it specifically regulates the mining sector. This situation raises a legal question regarding how the principles of lex specialis derogat legi generali, lex superior derogat legi inferiori, and lex posterior derogat legi priori should be interpreted and applied by the Government within the framework of Aceh as a Special Autonomous Region. This study aims to conduct an in-depth legal analysis using a progressive law approach to examine whether the principles of lex posterior or lex superior may override the principle of lex specialis as applied in Aceh’s special autonomy regime. The research employs normative legal methods with qualitative analysis. The findings indicate that the principle of lex specialis derogat legi generali as stipulated in the Law on the Governance of Aceh must take precedence due to its specific territorial applicability and special autonomous status. In resolving such normative conflicts, a clear legal framework is required, accompanied by the renewal of legal theories and principles to ensure legal certainty, prevent regulatory overlap, and promote harmony among statutory regulations.